The Tools for Intelligent Data Analysis, Modeling and Forecasting Of Social and Economic Processes - Savchenko-Synyakova, Ye.A.; Tutova, O.V. (Control systems & computers, 2021)
The tools of intellectual modeling in MS Excel are developed on the basis of a technique of the analysis, modeling and forecasting of difficult processes on a DB of social and economic processes which contains the information on the indicators characterizing development of digital economy of Ukraine. This will automate and improve the decision-making process in the field of socio-economic development of Ukraine both at the regional level and in comparison with other countries.